Energy balance in haemodialysis and peritoneal dialysis patients assessed by a 7‐day weighed food diary and a portable armband device. Issue 3 (28th November 2012) - Bovio, G.; Montagna, G.; Brazzo, S.; Piazza, V.; Segagni, S.; Cena, H.
Abstract Background Energy balance (EB) is important when assessing nutritional status. EB has never been assessed in haemodialysis (HD) and peritoneal dialysis (PD) patients. The present study aimed to assess weekly EB in these patients. Methods This clinical cross‐sectional study was conducted for 7 days in eight HD and eight PD patients. Nutritional status was assessed by anthropometry, bioelectrical impedance analysis and biochemical markers. Energy intake (EI per day) and total energy expenditure (TEE per day) were determined by a 7‐day weighed food diary and a portable armband device, respectively. Results No significant differences in age, body mass index, fat free mass (FFM), parathyroid hormone were found between the two groups. EB was calculated by subtracting TEE per day from EI per day. EB was negative in HD −1347 (1276) kJ day−1 [−322 (305) kcal day−1], as well as in PD patients −427 (5338) kJ day−1 [−102 (395) kcal day−1]. TEE per day was positively correlated with EI per day, prealbumin, FFM. EI per day was positively correlated with prealbumin. C‐reactive protein was negatively correlated with TEE and FFM (P < 0.05). EB showed a positive correlation with EI per day (P = 0.012) and a negative trend with TEE. Conclusions HD and PD patients have a negative EB and are at risk of malnutrition. Inflammatory status determines a lower EI per day and a reduction in TEE per day. The most important parameter in determining EB in HD and PD patients is EI per day. This topic deserves further investigation to better understand the mechanisms of impaired EB with respect to preserving patients' nutritional status.